Beyond the Woodward-Hoffman Rules: What Controls Reactivity in Eliminative Aromatic Ring-Forming Reactions? - Wonanke, A. D. Dinga; Crittenden, Deborah L. (Australian journal of chemistry, 2018)
The Mallory (photocyclization) and Scholl (thermal cyclohydrogenation) reactions are widely used in the synthesis of extended conjugated π systems of high scientific interest and technological importance, including molecular wires, semiconducting polymers, and nanographenes. While simple electrocyclization reactions obey the Woodward-Hoffman rules, no such simple, general, and powerful model is available for eliminative cyclization reactions due to their increased mechanistic complexity. In this work, detailed mechanistic investigations of prototypical reactions reveal that there is no single rate-determining step for thermal oxidative dehydrogenation reactions, but they are very sensitive to the presence and distribution of heteroatoms around the photocyclizing ring system. Key aspects of reactivity are correlated to the constituent ring oxidation potentials. For photocyclization reactions, planarization occurs readily and/or spontaneously following photo-excitation, and is promoted by heteroatoms within 5-membered ring adjacent to the photocyclizing site. Oxidative photocyclization requires intersystem crossing to proceed to products, while reactants configured to undergo purely eliminative photocyclization could proceed to products entirely in the excited state. Overall, oxidative photocyclization seems to strike the optimal balance between synthetic convenience (ease of preparation of reactants, mild conditions, tolerant to chemical diversity in reactants) and favourable kinetic and thermodynamic properties.